The role of prison in relation to national security - Carou García, Sara (Journal of the Spanish Institute for Strategic Studies, 2020)
The present text analyses the role played by the prison within the state’sstructure, aimed at preserving National Security. This is analyzed the purposes attributed to the prison by the Spanish Constitution. It also examines,from a legal point of view, the possibilities of obtaining information insidethe penitentiary centres which, once analyzed, lead to the elaboration ofcriminal intelligence.
Keywords: Prison; National Security; security measures; information; criminal intelligence